(E)‐3‐tert‐Butyl‐4‐(4‐chlorobenzyl)‐N‐(4‐chlorobenzylidene)‐1‐phenyl‐1H‐pyrazol‐5‐amine: sheets built from π‐stacked hydrogen‐bonded dimers. (5th August 2013) - Quiroga, Jairo; Pantoja, Dayana; Cobo, Justo; Glidewell, Christopher
Abstract : The title compound, C27 H25 Cl2 N3, is an unexpected but high‐yield product from the microwave‐mediated reaction between 3‐ tert ‐butyl‐ N ‐4‐chlorobenzyl‐1‐phenyl‐1 H ‐pyrazol‐5‐amine and 4‐chlorobenzaldehyde. Inversion‐related pairs of molecules are linked by C—H...π(arene) hydrogen bonds to form cyclic centrosymmetric dimers, and dimers of this type are linked into sheets by two independent π–π stacking interactions.